2015
DOI: 10.3758/s13421-015-0578-3
|View full text |Cite
|
Sign up to set email alerts
|

Competition dependence of retrieval-induced forgetting in motor memory

Abstract: In two experiments, we examined the competition dependence of retrieval-induced forgetting (RIF) in motor memory. Participants learned sequential finger movements as responses to letter stimuli. The learning phase comprised two parts. In both parts, half of the motor sequences were to be executed at one of two locations (the left or right side of a keyboard) by pressing the corresponding response keys. Retrieval practice of half of the motor sequences at one location induced forgetting of the nonpracticed moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Take, for example, the popular forgetting phenomenon retrieval-induced forgetting. Retrieval-induced forgetting was originally demonstrated with words (Anderson et al, 1994), but has been shown to generalize to a variety of materials such as visual-spatial objects (Ciranni & Shimamura, 1999), eyewitness memories (Shaw, Bjork, & Handal, 1995), motor memory (Tempel, Aslan, & Frings, 2016), and location information (Gómez-Ariza, Fernandez, & Bajo, 2012). Given that the above-named theories of forgetting attempt to account for retrieval-induced forgetting, the many stimulus types susceptible to this forgetting effect may be a liability in elucidating the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Take, for example, the popular forgetting phenomenon retrieval-induced forgetting. Retrieval-induced forgetting was originally demonstrated with words (Anderson et al, 1994), but has been shown to generalize to a variety of materials such as visual-spatial objects (Ciranni & Shimamura, 1999), eyewitness memories (Shaw, Bjork, & Handal, 1995), motor memory (Tempel, Aslan, & Frings, 2016), and location information (Gómez-Ariza, Fernandez, & Bajo, 2012). Given that the above-named theories of forgetting attempt to account for retrieval-induced forgetting, the many stimulus types susceptible to this forgetting effect may be a liability in elucidating the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, offline contexts modulate retrieval, although the context is not presented when the retrieval takes place. For instance, in the retrieval-induced forgetting and directed-forgetting paradigms (Anderson, Bjork, & Bjork, 1994;Bjork, 1972;Burwitz, 1974), it is assumed that retrieval practice or a forget instruction for a particular list of items induces a context change that modulates the retrieval of a subsequent list of items (notwithstanding that other processes might also contribute to these memory effects; e.g., Tempel, Aslan, & Frings, 2016). Yet, offline contexts could also include external information-for example, in cued recall, if the cue is presented just before the participant has to retrieve a particular item.…”
mentioning
confidence: 99%
“…By adapting paradigms from memory research to the use of motor sequences as item material, we found that retrieval can shape motor memory in opposing ways by demonstrating retrieval-induced forgetting as well as test-potentiated learning (Tempel, Aslan, & Frings, 2016;Tempel & Frings, 2013, 2014a, 2014b, 2016aTempel, Loran, & Frings, 2015;Tempel & Kubik, 2017). Thus, retrieval effects extend to motor memory.…”
Section: Introductionmentioning
confidence: 86%